A methodology for carbamate post-translational modification discovery and its application in Escherichia coli. Issue 2 (12th February 2021) - Linthwaite, Victoria L.; Cann, Martin J.
Abstract : Carbon dioxide can influence cell phenotypes through the modulation of signalling pathways. CO2 regulates cellular processes as diverse as metabolism, cellular homeostasis, chemosensing and pathogenesis. This diversity of regulated processes suggests a broadly conserved mechanism for CO2 interactions with diverse cellular targets. CO2 is generally unreactive but can interact with neutral amines on protein under normal intracellular conditions to form a carbamate post-translational modification (PTM). We have previously demonstrated the presence of this PTM in a subset of protein produced by the model plant species Arabidopsis thaliana . Here, we describe a detailed methodology for identifying new carbamate PTMs in an extracted soluble proteome under biologically relevant conditions. We apply this methodology to the soluble proteome of the model prokaryote Escherichia coli and identify new carbamate PTMs . The application of this methodology, therefore, supports the hypothesis that the carbamate PTM is both more widespread in biology than previously suspected and may represent a broadly relevant mechanism for CO2 –protein interactions.